2007
DOI: 10.1080/01140670709510190
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of what the consumer values in fresh fruit quality: Case study of Oman

Abstract: The health and nutritional benefits of fruit consumption are well documented in the scientific literature. Understanding consumer perceptions and attitudes towards fruit quality is important in setting quality specifications for marketing as well as providing a useful guide for postharvest research aimed at quality improvement of fresh produce. In this study, we investigated the frequency of fruit consumption and consumer perceptions of fruit quality in the Sultanate of Oman using self-administered questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…This pattern of light consumers being the most common category was consistent across all cities. These findings concur with those of Opara et al (2007) who reported frequent consumption of fruits. …”
Section: Level and Frequency Of Consumptionsupporting
confidence: 91%
See 1 more Smart Citation
“…This pattern of light consumers being the most common category was consistent across all cities. These findings concur with those of Opara et al (2007) who reported frequent consumption of fruits. …”
Section: Level and Frequency Of Consumptionsupporting
confidence: 91%
“…Over time, consumer perceptions of food quality have broadened, and nowadays consumers consider not only core product attributes, but also food safety and attributes related to marketing (Opara et al 2007;Ali et al 2010;Larsen 2014). As a result, the identification of relevant attributes is considered a major challenge in consumer studies.…”
Section: Mango Quality Attribute Preferencesmentioning
confidence: 99%
“…Surveys have identifi ed the lack of consistent quality as a major reason people do not buy peaches (Byrne 2005 ) . In addition, there is a willingness of consumers to pay more for better quality (Opara et al 2007 ) , which is the reason for developing branded fruit that consistently delivers quality fruit (Jaeger 2006 ) .…”
Section: Consumer Expectations and Habitsmentioning
confidence: 99%
“…To maximize the consumption of fruit, high quality needs to be delivered consistently as previous experience infl uences future purchasing decisions (Racskó et al 2009 ;Poole and Baron 1996 ) . There is evidence that consumers are willing to pay more for signifi cantly better tasting fruit (Gamble et al 2006 ;Opara et al 2007 ) .…”
Section: Consistent High Fruit Qualitymentioning
confidence: 99%
“…Wadolowska et al (2008) identified that factors affecting food choice depended on the types of products. Opara et al (2007) determined consumer preferences of five types of fruit using questionnaires among the Omani population. They found that the most influential quality attributes affecting consumer preference were flavor, sweetness, and color for bananas and dates; and flavor, sweetness, and firmness for apples, mangos, and oranges.…”
Section: Importance Of Attributes (Rank)mentioning
confidence: 99%